Isolation and characterization of small colony variants of Staphylococcus aureus in various food samples. (August 2021) - Hussain Chan, Malik Wajid; Mirani, Zulfiqar Ali; Khan, Muhammad Naseem; Ali, Amjad; Khan, Abdul Basit; Asadullah; Rauf, Naseem
Abstract: Staphylococcus aureus is one of the major foodborne pathogen. It may persist for a long time in harsh environment and is responsible for deterioration of food quality (texture, color and taste). The present study is designed to investigate the survival strategy of S. aureus in acidic and sweet based food items. The food samples showed <10 colony forming units CFU/mL through conventional methods. Therefore, resuscitation method was applied to recover metabolically inactive or mutant isolates. Food samples consisted of 61 mango squash (pH = 4.5), 32 sweet mixes (pH = 4.5), 6 canned food (pH = 5.0), 6 bakery items (pH = 5.0) and 9 other food items including ready to eat meal and vermicelli (pH = 4.5–5.0). The Resuscitation method showed the growth of S. aureus in 12 (19.6%) mango squash samples, 7 (31.8%) sweet mixes, 1 (16.6%) canned food, 3 (50.0%) bakery items and 3 (33.3%) other food items. Out of 12 mango squash, 7 samples showed the growth of Wild type (WT) and small colony variants (SCVs), whereas 5 samples showed only WT colonies. The majority (5 out of 7 samples) of the sweet mix showed WT colonies and only 2 samples showed mixed growth of WT and SCVs. WT isolates were oxacillin sensitive, while SCVs were oxacillin resistant. Similarly, SCVs exhibited higher MICs against Ascorbic Acid and Potassium Sorbate. Furthermore, SCVs adapted biofilm to survive under hostile environment. This study shows that conversion to SCVs and biofilm life style is the survival strategy of S. Aureas to persist for a long time in acidic or unfavorable environment. Highlights: The resuscitation method was applied to recover metabolically inactive isolates. Wild type (WT) and small colony variants (SCVs) isolates were obtained. WT isolates were oxacillin sensitive while SCVs were oxacillin resistant. SCVs adapted biofilm mode of life to survive under hostile environment. Biofilm formation is survival strategy of Staphylococcus aureus in harsh conditions.